DETERMINANTS OF PURCHASE INTENTION IN NFT MARKETPLACES: THE CENTRAL ROLE OF TRUST IN MAGIC EDEN - Ronansa Vaza Bramudya; Ratna Roostika; Syafie, Nur Aima (UIN Sunan Gunung Djati Bandung, 2026)
The rapid growth of non-fungible tokens (NFTs) has increased competition among digital marketplaces and heightened the need to understand factors that drive consumer purchase intention. However, NFT platforms still face challenges related to technological complexity and trust, which may hinder user participation. This study examines the effects of social influence, effort expectancy, performance expectancy, and trust on purchase intention in the Magic Eden NFT marketplace using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. This research contributes by extending the UTAUT model to the NFT marketplace context and highlighting the pivotal role of trust in shaping user perceptions and behavioral intentions. A quantitative approach was employed by collecting data from 251 Magic Eden users through an online questionnaire distributed via social media and crypto communities. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS to test the proposed relationships. The results indicate that social influence, effort expectancy, and performance expectancy have significant positive effects on purchase intention. Trust also has a strong positive effect on effort expectancy and performance expectancy, as well as a direct positive effect on purchase intention. Among the examined relationships, trust shows the strongest influence on users’ perceived ease of use of the platform. Overall, the findings suggest that strengthening trust and improving platform usability are essential for increasing purchase intention in NFT marketplaces.